Evaluation of rotigotine transdermal patch for the treatment of depressive symptoms in patients with Parkinson's disease. (23rd July 2016) - Chung, Sun Ju; Asgharnejad, Mahnaz; Bauer, Lars; Ramirez, Francisco; Jeon, Beomseok
ABSTRACT: Objective : To evaluate the dopamine receptor agonist, rotigotine, for improving depressive symptoms in patients with Parkinson's disease (PD). Methods : Patients were randomized 1:1 to rotigotine or placebo, titrated for ≤7 weeks, and maintained at optimal/maximum dose for 8-weeks. Primary efficacy variable: 17- item Hamilton Depression Rating Scale (HAM-D 17) total score change from baseline to end-of-maintenance. Secondary variables: changes in Beck Depression Inventory-II, Unified Parkinson's Disease Rating Scale (UPDRS) II (activities of daily living [ADL]) and III (motor) subscores, UPDRS II+III total, patient-rated Apathy Scale (AS), and Snaith-Hamilton Pleasure Scale. Results : Of 380 patients randomized, 149/184 (81.0%) rotigotine-treated and 164/196 (83.7%) placebo-treated patients completed the study. Patients: mean (±SD) age 65.2 (±8.5) years; time since PD-diagnosis 2.74 (±3.08) years; 42.6% male. The treatment difference (LS mean [95% CI]) in change from baseline HAM-D 17 was −1.12 (−2.56, 0.33; p = 0.1286). UPDRS II, III, II+III and AS scores improved numerically with rotigotine versus placebo. Common adverse events with higher incidence with rotigotine: nausea, application/instillation site reactions, vomiting, and pruritus. Forty-one (10.8%) patients discontinued owing to adverse events (25 rotigotine/16 placebo). Conclusions : No statistically significant improvement in depressive symptoms were observed with rotigotine versus placebo. ADL, motor function, and patient-rated apathy improved numerically. ClinicalTrials.gov: NCT01523301